2002
DOI: 10.1177/000331970205300613
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Vasodilatory Dysfunction in Adult Patients with Congenital Heart Disease and Severely Elevated Pulmonary Vascular Resistance

Abstract: Several studies have demonstrated that pulmonary vascular abnormalities precede alterations in aortic circulation downstream in animal models of heart failure. The relationship between increased pulmonary vascular resistance (PVR) and agonist-induced limb vasodilatory response remains unknown in patients with congenital cardiovascular shunt lesions (CSL). The authors hypothesized that patients with CSL and severely elevated PVR will show a defective vasomotor response in the peripheral vascular bed. To examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
(5 reference statements)
0
6
1
Order By: Relevance
“…The growing evidence from studies performed in patients with IPAH and scleroderma-PAH suggest the presence of a wide spectrum of systemic metabolic and inflammatory alterations and vascular dysfunction (5,6, manifested by Impaired brachial artery vasodilatory reserve (5,6,(15)(16)(17)(18)(19)(20)(21)(22). Blood flow abnormalities in the middle cerebral artery, reduced cerebrovascular reactivity to blood PCO 2 , decreased NO production by cerebral endothelial cells, impairment in perception of dyspnea and sleep-disordered breathing (5,6,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The growing evidence from studies performed in patients with IPAH and scleroderma-PAH suggest the presence of a wide spectrum of systemic metabolic and inflammatory alterations and vascular dysfunction (5,6, manifested by Impaired brachial artery vasodilatory reserve (5,6,(15)(16)(17)(18)(19)(20)(21)(22). Blood flow abnormalities in the middle cerebral artery, reduced cerebrovascular reactivity to blood PCO 2 , decreased NO production by cerebral endothelial cells, impairment in perception of dyspnea and sleep-disordered breathing (5,6,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Flow-mediated dilatation (FMD) was first described in femoral and brachial arteries and is mediated by potassium channel dependent release of NO produced from the nitroglycerine that leaks into the smooth muscle cells (5,6,(14)(15)(16)(17)(18)(19)(20). ED-FMD (ischemia response) assesses the hyperemia occurring in medium muscular arteries as a response to shear stress following ischemia induced by inflating the blood pressure cuff (5,6,(14)(15)(16)(17)(18)(19)(20). In patients with PAH, studies with duplex ultrasound in BA revealed impaired FMD as a marker for systemic endothelial disfunction (5,6,(14)(15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations